2008
DOI: 10.1152/ajpgi.00123.2007
|View full text |Cite
|
Sign up to set email alerts
|

Why does the gut choose apolipoprotein B48 but not B100 for chylomicron formation?

Abstract: Chylomicrons produced by the human gut contain apolipoprotein (apo) B48, whereas very-low-density lipoproteins made by the liver contain apo B100. To study how these molecules function during lipid absorption, we examined the process as it occurs in apobec-1 knockout mice (able to produce only apo B100; KO) and in wild-type mice (of which the normally functioning intestine makes apo B48, WT). Using the lymph fistula model, we studied the process of lipid absorption when animals were intraduodenally infused wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 42 publications
6
99
0
1
Order By: Relevance
“…ApoB100 has 4536 amino acids. ApoB48 results from a post-transcriptional modification of the apoB mRNA, through the action of the APOB mRNA editing complex (APOBEC1) which forms a stop codon at approximately 48% of the full length coding sequence [43]. The truncated form of ApoB100, ApoB48 lacks the C-terminus which contains the domain recognized by the LDL receptor.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%
“…ApoB100 has 4536 amino acids. ApoB48 results from a post-transcriptional modification of the apoB mRNA, through the action of the APOB mRNA editing complex (APOBEC1) which forms a stop codon at approximately 48% of the full length coding sequence [43]. The truncated form of ApoB100, ApoB48 lacks the C-terminus which contains the domain recognized by the LDL receptor.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%
“…The C terminus of apoB 100 contains the domain recognized by the LDL receptor, thereby mediating high-affinity clearance of these particles from plasma. In contrast, essentially all of the apoB from human intestine appears as a truncated form, apoB 48 , that is missing the C-terminal 52% (37), and so CMs and CM remnants rely on exchangeable proteins, particularly lipoprotein lipase (LpL; refs. 38-41), hepatic lipase (42,43), and apoE (44)(45)(46), to serve as ligands for cell surface receptors.…”
Section: Intestinal Packaging Of Absorbed Lipids Into Apob 48 -Contaimentioning
confidence: 99%
“…Polymorphisms of each of these exchangeable proteins affect fasting lipoprotein concentrations (47) and the postprandial response (43). Intestinal apoB 48 comes from the same gene as apoB 100 through the action of the APOB mRNA editing complex-1 (APOBEC1), which deaminates a single cytidine into a uridine, thereby creating a nongenomic inframe stop codon (UAA) roughly in the middle of the RNA coding region ( Figure 2 and ref. 48).…”
Section: Intestinal Packaging Of Absorbed Lipids Into Apob 48 -Contaimentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency of apobec-1 in the intestine resulted in reduction in the secretion and assembly of chylomicron particles (Kendrick, 2001). These results from apobec-1-KO mice suggested that apoB-48 is involved in the assembly of chylomicron particles (Lo, 2008). Finally, absorbed lipids and synthesized apolipoproteins are assembled by MTP.…”
Section: Cholesterol Absorption In the Intestinementioning
confidence: 96%